El ave como cielo: la presencia del ave chan en las bandas celestes mayas - Rogelio Valencia Rivera; Daniel Salazar Lama (Journal de la Société des Américanistes)
In Mayan pictorial tradition, the use of certain iconographic elements serves to transmit messages with a high symbolic content, whether these messages refer to mythological narratives, or illustrate historical events that approximate mythical ones. Due to the fact that some iconographic elements possess an inherent multivalued symbolic content (i.e. they are polysemic), sometimes the Maya painters or sculptors used writing to denote univocally the element they tried to represent. Because of the highly figurative character of Maya glyphs, they integrated gracefully with the different iconographic elements, giving the whole piece a uniformity that was not broken by the introduction of writing. We can find one example of this with the denotation of iconography in Sky Bands adorned with bird’s heads, the subject of the present paper. These bird’s heads could be of two types, one with a hand as the inferior mandible and the other wearing a mirror on its forehead. The analysis provided in the paper demonstrates that both were used as the logogram CHAN, “sky”, to indicate in a very clear and unambiguous way that the bands they were represented with refer to a celestial environment.